EFFECT OF DIFFERENT STAND ESTABLISHMENT TECHNIQUES ON RICE YIELDS AND ITS ATTRIBUTES - M. Aslam; S. Hussain; M. Ramzan; M. Akhter (Journal of Animal and Plant Sciences, 2008)
To investigate the effect of various rice stand establishment techniques viz; double zero tillage, direct seeding of rice, brown manuring, transplanting on beds and conventional transplanting, the experiments were conducted at Chak 37 and Kot Nazir, Distt. Sheikhupura during 2006. The highest number of productive tillers/unit even (231.7) were noted in direct seeding followed by double zero tillage (219), bed planting (206.7) and conventional planting (200.2) respectively. Direct seeded crop produced smaller panicles that bore less number of grains (72.67) and grain weight (22.17g) which resulted lower grain yield. The crop established with double zero tillage produced the highest paddy yield (4.8 t/ha) that was statistically at par with conventionally planted crop (4.72 t/ha). The paddy yield in bed planting (4.43 t/ha) and brown manuring (4.23 t/ha) were at par and significantly higher than direct seeding (3.36 t/ha) that produced the lowest yield. The highest cost benefit ratio (1:1.91) was observed in double zero tillage.
Keywords: Attributes; zero tillage; direct seeding; brown manuring